Interstitial brachytherapy technique for chest wall refractory recurrence of breast cancer - Wu, Ning; Chen, Qianqian; Zhao, Zhipeng; Zhao, Hongfu; Cheng, Guanghui (Journal of Contemporary Brachytherapy, 2015)
Purpose : To report the treatment effect of interstitial brachytherapy for chest wall locoregional recurrence of breast cancer. Material and methods : This 44-year-old female presented with chest wall recurrence seven years after modified radical mastectomy for stage II breast cancer. Despite external beam radiation and chemotherapy, the lesion expanded as 5.3 × 5.1 × 3.0 cm 3 , and 8.0 × 5.1 × 4.0 cm 3 . The locoregional recurrent tumor was treated with interstitial brachytherapy under ultrasound guidance. The brachytherapy dose was 30 Gy in 6 fractions of 5 Gy each. Results : Removal of the recurrent tumor was securely achieved by interstitial brachytherapy guided with ultrasound scanning. The refractory tumor in patient healed uneventfully after interstitial brachytherapy without recurrence during the 7 months of follow-up. Conclusions : The ultrasound-guided interstitial brachytherapy may be effective for refractory recurrence of breast cancer.